Statistical Insights from Marine Exports in India: An Economic Analysis - , Suman, L.; Ajayakumar, Hamsa, K.R., Manojkumar Patil; Sagar (Archives of Current Research International, 2024)
This paper investigates the performance of marine products exported from 1995-2022, in terms of both quantity and value, identify trends, and assess market volatility using metrics viz., CAGR and CDVI. The analysis reveals a substantial overall increase in export volumes, with total quantities rising by 485.70 per cent over the period, driven largely by a 642.86 per cent growth in Frozen Shrimp exports. Export values have also seen a dramatic rise, with Frozen Shrimp's value growing by 1730.25 per cent to Rs. 43,135.58 crore. Despite this growth, the market exhibits significant erraticism, particularly in high-value segments viz., Frozen Shrimp, which shows a CDVI of 99.41, indicating instability. Employing multiple models for both quantities and value of exports, the exponential model found to be best in capturing trend with lowest RMSE, AIC, BIC and the highest Adjusted R², highlighting it’s ability to accurately capture the growth patterns in marine exports. Thus, it indicated the presence of exponential growth pattern in marine exports. In India’s marine export sector, particularly segments like dried and chilled items, offers significant potential for further expansion and diversification. These insights are critical to develop strategies to sustain growth while managing the risks associated with market dynamics. Thus, findings give valuable inputs for policymakers and stakeholders in strategic planning to capitalize on growth opportunities while addressing market instability.